2017
DOI: 10.1007/s00787-017-0986-y
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of quality of life and functional outcomes in randomized placebo-controlled studies of medications for attention-deficit/hyperactivity disorder

Abstract: Children, adolescents and adults with attention-deficit/hyperactivity disorder (ADHD) experience functional impairment and poor health-related quality of life (HRQoL) in addition to symptoms of inattention/hyperactivity–impulsivity. To synthesize qualitatively the published evidence from randomized, double-blind, placebo-controlled trials of the effectiveness of pharmacotherapy on functional impairment or HRQoL in patients with ADHD, a systematic PubMed searching and screening strategy was designed to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 99 publications
4
65
0
3
Order By: Relevance
“…Future studies should extend our data to larger samples of low-and high-dose BZD/Z-drug users through a multicenter design. Since pharmacological treatment may help reduce QoL impairment in ADHD patients [51], longitudinal studies should explore whether appropriate BZD/Z-drug detoxification might improve QoL measures and whether the most appropriate detoxification protocol differ in ADHD+ versus ADHD− populations.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should extend our data to larger samples of low-and high-dose BZD/Z-drug users through a multicenter design. Since pharmacological treatment may help reduce QoL impairment in ADHD patients [51], longitudinal studies should explore whether appropriate BZD/Z-drug detoxification might improve QoL measures and whether the most appropriate detoxification protocol differ in ADHD+ versus ADHD− populations.…”
Section: Discussionmentioning
confidence: 99%
“…62 It is critical to treat ADHD early and effectively to minimize harm and increase a patient's quality of life. 42,44,63 It is also important to note that pharmacotherapy is just one component of an ADHD treatment plan. For instance, in preschool-aged children with ADHD, the recommended first line of treatment is behavioral therapy and methylphenidate should be prescribed only if the behavioral interventions do not provide sufficient improvement and moderate-to-severe disturbances continue to affect the child's function.…”
Section: Treatment Reduces the Risk Of Morbidity And Mortality And Inmentioning
confidence: 99%
“…There is evidence that psychostimulants including methylphenidate have a moderate-to-large short-term (i.e., up to 16 weeks) effect on the management of oppositional behavior, conduct problems, and aggression in children and adolescents with ADHD with or without comorbid oppositional-deviant disorder (ODD) or conduct disorder (Pringsheim et al, 2015). Furthermore, systematic reviews concluded that there may be a short-term positive effect of ADHD medication on QoL in children and adolescents (Coghill, 2010;Coghill et al, 2017). However, the effect sizes are smaller than seen for ADHD symptoms and almost exclusively based on studies examining atomoxetine.…”
Section: Introductionmentioning
confidence: 99%